Analisis Kinerja Fungsional pada Aplikasi Mobile JKN Melalui Pengujian Black Box Testing - Ratna Santika; Santi Febrianti; Sam’un Hakeki; Udan; Yusup Supriyanto; Zidan Fajar Abdillah; Subhanjaya Angga Atmaja (PT Pustaka Cendekia Group, 2025)
Digital transformation in Indonesia's health sector has accelerated significantly since the implementation of the National Health Insurance (JKN) program by BPJS Kesehatan, particularly through the Mobile JKN application. This application aims to simplify public access to health services and information; however, various technical issues are still frequently encountered. This study aims to evaluate the functional performance of the Mobile JKN application using the Black Box Testing method, specifically the Equivalence Partitioning and Boundary Value Analysis techniques. The research adopts a qualitative descriptive approach through participatory observation of the latest version of the application. The testing focuses on core features such as registration, login, healthcare service registration, and user data modification. Test results are categorized into three outcomes: fully functional, partially functional, and non-functional. The findings show that most features operate properly and as expected, while the system also consistently rejects invalid inputs. This research contributes theoretically to the literature on e-health software testing and provides practical recommendations for developers and policymakers to enhance the quality of BPJS Kesehatan’s digital services.